PSYCHOPHYSIOLOGICAL STATUS OF THE DRIVER AS A STOCHASTIC FACTOR OF TRAFFIC - Бурлакова, Г.; Ганжеев, Д. (SWorldJournal, 2022)
The "human factor" remains one of the main stochastic factors affecting road safety. To reduce adverse effects, as well as to take into account the individual physical, psychological, behavioral and other characteristics of drivers in monitoring and oper